Extracellular Electron Transfer via Outer Membrane Cytochromes in a Methanotrophic Bacterium Methylococcus capsulatus (Bath) - Tanaka, Kenya; Yokoe, Sho; Igarashi, Kensuke; Takashino, Motoko; Ishikawa, Masahito; Hori, Katsutoshi; Nakanishi, Shuji; Kato, Souichiro (Frontiers in Microbiology, 2018)
Electron exchange reactions between microbial cells and solid materials, referred to as extracellular electron transfer (EET), have attracted attention in the fields of microbial physiology, microbial ecology, and biotechnology. Studies of model species of iron-reducing, or equivalently, current-generating bacteria such as Geobacter spp. and Shewanella spp. have revealed that redox-active proteins, especially outer membrane c-type cytochromes (OMCs), play a pivotal role in the EET process. Recent (meta)genomic analyses have revealed that diverse microorganisms that have not been demonstrated to have EET ability also harbor OMC-like proteins, indicating that EET via OMCs could be more widely preserved in microorganisms than originally thought. A methanotrophic bacterium Methylococcus capsulatus (Bath) was reported to harbor multiple OMC genes whose expression is elevated by Cu starvation. However, the physiological role of these genes is unknown. Therefore, in this study, we explored whether M. capsulatus (Bath) displays EET abilities via OMCs. In electrochemical analysis, M. capsulatus (Bath) generated anodic current only when electron donors such as formate were available, and could reduce insoluble iron oxides in the presence of electron donor compounds. Furthermore, the current-generating and iron-reducing activities of M. capsulatus (Bath) cells that were cultured in a Cu-deficient medium, which promotes high levels of OMC expression, were higher than those cultured in a Cu-supplemented medium. Anodic current production by the Cu-deficient cells was significantly suppressed by disruption of MCA0421, a highly expressed OMC gene, and by treatment with CO gas (an inhibitor of c-type cytochromes). Our results provide evidence of EET in M. capsulatus (Bath) and demonstrate the pivotal role of OMCs in this process. This study raises the possibility that EET to solid compounds is a novel survival strategy of methanotrophic bacteria.